1995
DOI: 10.1093/nar/23.13.2361
|View full text |Cite
|
Sign up to set email alerts
|

3-Nitropyrrole and 5-nitroindole as universal bases in primers for DNA sequencing and PCR

Abstract: 3-Nitropyrrole and 5-nitroindole have been assessed as universal bases in primers for dideoxy DNA sequencing and in the polymerase chain reaction (PCR). In contrast to a previous report, we have found that the introduction of more than one 3-nitropyrrole residue at dispersed positions into primers significantly reduced their efficiency in PCR and sequencing reactions. Primers containing 5-nitroindole at multiple dispersed positions were similarly affected; for both bases only a small number of substitutions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 9 publications
2
71
1
Order By: Relevance
“…In the case of XPA protein, we observed preferential binding not only to carcinogen-damaged or mismatched substrates but, with higher efficiency, also to duplexes containing 5-nitroindole and 3-nitropyrrole residues. These aromatic base analogs lack hydrogen acceptors and donors for Watson-Crick strand pairing and, therefore, generate nonhybridizing sites characterized by increased hydrophobicity (26). Thus, the affinity of XPA for duplexes containing such aromatic analogs suggests that its strong bias for displaced pairing conformations is mediated by hydrophobic interactions with aromatic base components that are abnormally exposed to the helical surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of XPA protein, we observed preferential binding not only to carcinogen-damaged or mismatched substrates but, with higher efficiency, also to duplexes containing 5-nitroindole and 3-nitropyrrole residues. These aromatic base analogs lack hydrogen acceptors and donors for Watson-Crick strand pairing and, therefore, generate nonhybridizing sites characterized by increased hydrophobicity (26). Thus, the affinity of XPA for duplexes containing such aromatic analogs suggests that its strong bias for displaced pairing conformations is mediated by hydrophobic interactions with aromatic base components that are abnormally exposed to the helical surface.…”
Section: Discussionmentioning
confidence: 99%
“…4A). However, their aromatic ring structures have a similar electron distribution as natural bases and, as a consequence, retain at least in part the potential for hydrophobic interactions (26). When three consecutive 5-nitroindole (Fig.…”
Section: Binding Of Xpa Protein To Artificially Denatured Basementioning
confidence: 99%
“…Similar behavior exhibit 2'-deoxyinosine analogues: 7-deaza-2'-deoxyinosine [5] and 2-aza-2'-deoxyinosine [6]. Melting studies of oligonucleotides containing the deoxyribonucleotides of 3-nitro-1H-pyrrole [7 ± 9], 4-, 5-, or 6-nitro-1H-indole [10,11] or 4-nitro-1H-imidazole [12] have demonstrated that the nitroazoles show less discrimination in their base pairs with the four natural bases than other types of analogues investigated as universal base candidates. To study base-pairing properties azolecarboxamides were also investigated [13 ± 16].…”
mentioning
confidence: 88%
“…We believe, however, that they also stabilise duplexes predominantly by stacking interactions, and are therefore also valuable for studying the nature of non-covalent interactions within the double helix. Some of these analogues have been shown to be effective in some molecular biology applications, notably in PCR and sequencing (Bergstrom et al, 1995;Loakes et al, 1995;Parinov et al, 1996). Thus far, none of the`nonhydrogen bonding' bases has been shown to be an enzyme substrate, nor have their properties in templates been de®ned.…”
Section: Introductionmentioning
confidence: 99%